PENGARUH BRAND IMAGE DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN SHOPEE (STUDI PADA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS MULAWARMAN) - Putri, Rini Ardah; Ellyawati, Noor; Permatasari, Indah (Educational Studies: Conference Series, 2023)
This research aims to determine the Influence of Brand Image and Brand Trust on the Purchase Decisions of Shopee Customers with a Study on Students of the Economics Education Program at Mulawarman University. This type of research is associative, employing a quantitative approach. The sample in this study consists of 86 respondents selected using the Purposive Sampling technique. Data collection technique involves using questionnaires. The analysis method used in this study is Multiple Linear Regression Analysis. The results of this study indicate that the brand image (X1) partially has a positive and significant impact on Shopee customers' purchase decisions (Y), and the brand trust (X2) partially has a positive and significant impact on Shopee customers' purchase decisions (Y). In the coefficient of determination (R²) test, it is found that the combined influence of brand image and brand trust on Shopee customers' purchase decisions is 49.8%. The remaining 50.2% is influenced by variables outside of Brand Image and Brand Trust, such as price and convenience.